The use of statistics to identify the socioeconomic and cultural profile of students entering an undergraduate course at a Federal Rural University of the Amazon (Research, Society and Development, 2021)
Knowing the socioeconomic and cultural profile of higher education students has been one of the ways these students avoid giving up on their undergraduate courses. Because of this, this research aims to identify the social, economic and cultural reality of undergraduate students in Animal Science at the Federal Rural University of Amazônia, campus of Parauapebas (UFRA). Information was collected from 32 of the 35 students enrolled in the first semester of the 2020 course. It was identified that the average age of newcomers to the zootechnics course is 20 years and many come from other cities and even states. There is also the precarious access of these students to resources that can facilitate their performance in the course, in addition, a worrying fact is the relation to psychological symptoms suffered, as a good portion of these students suffer from some psychological symptom, which can directly affect in a possible evasion of the course. Difficulties in exact science subjects during high school were also verified, which can make this student have even greater difficulties during graduation.